Dynamics in Logistics Proceedings of the 4th International Conference LDIC, 2014 Bremen, Germany - Kotzab, Herbert; Pannek, Jürgen; Thoben, Klaus-Dieter.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This contributed volume brings together research papers presented at the 4th International Conference on Dynamics in Logistics, held in Bremen, Germany in February 2014. The conference focused on the identification, analysis and description of the dynamics of logistics processes and networks. Topics covered range from the modeling and planning of processes, to innovative methods like autonomous control and knowledge management, to the latest technologies provided by radio frequency identification, mobile communication, and networking. The growing dynamic poses wholly new challenges: logistics processes and networks must be(come) able to rapidly and flexibly adapt to constantly changing conditions. The book primarily addresses the needs of researchers and practitioners from the field of logistics, but will also be beneficial for graduate students.
A Micro- and Macro-Economic View on Shared Resources in Logistics -- The Regulation of Shared Resources - Impacts on the Logistics Sector -- Shared Transport Systems - A new Chance for Intermodal Freight Transport? -- Application of Topological Network Measures in Manufacturing Systems -- Optimization of a Factory Line using Multi Objective Evolutionary Algorithms.-Managing the Life Cycle of IT-Based Inter-firm Resources in Production and Logistics Networks -- Autonomous Control Strategy for High Precision Marking of Drill Holes using a Mobile Robot.
Keywords: Industrial Management; Production management; Application software; Mathematical models; Industrial Management; Operations Management; Computer and Information Systems Applications; Mathematical Modeling and Industrial Mathematics